Membrane capacitance in hyperpolarized muscle fibres. - Huang, C L (1981)
1. Voltage clamp experiments on muscle fibres compared transients to 10 mV steps at hyperpolarized voltages between VT = -100 to -185 mV with controls obtained at VC = -85 mV. 2. Membrane capacitance fell by 15%, 13% and 4.5% per 100 mV hyperpolarization fro -85 mV in hypertonic low chloride, hypertonic high chloride and isotonic high chloride-containing solutions respectively. 3. The charge moved by the 'on' and 'off' parts of the applied step was equal over the voltages studied. This suggests that the changes were capacitative rather than ionic in origin. The changes could not be explained in terms of the cable properties of the transverse tubular system. They may therefore reflect non-linear capacitance in the muscle membrane itself. 4. Subtracting control transients at -85 mV from transients obtained at different voltages gave monotonically decaying charge movements. In the frequency domain, these charge movements possessed real and imaginary permittivities resembling those of a 'Debye' particle. 5. It is concluded that muscle membranes have non-linear capacitances even at voltages far hyperpolarized to those in which familiar voltage-dependent processes occur.